Organic modification of titania sol-gels and surfaces - Pegg, E; Farrar, D; Scotchford, C; Walker, G; Grant, D (Trans Tech Publications, 2006)
Titanium and its alloys are commonly used biomaterials for bone contacting applications, the self-passivating titanium oxide surface producing a favourable non-specific response. The surface of a biomaterial is the first point of contact when implanted and hence is an crucial factor in determining the overall bodily response. By altering surface chemistry it is possible to control cell behaviour and promote desired cell responses [1]. In this study a process to attach peptides to titania is investigated with the aim to improve cell adhesion. The reaction with both titania surfaces and nano-particulate (5 nm) titania sols were investigated. Titania surfaces with a variety of hydroxyl group concentrations were reacted with 3%v/v aminosilane through an anhydrous route. FTIR and XPS results indicate successful attachment of aminosilane on all surfaces. Titania sols were reacted with aminosilane in their aqueous solution and subsequently cysteine attached using a cross-linker (sulfo-SMCC). The functionalised particles were analyzed using FTIR, results indicate successful attachment of silane and cross-linking of cysteine, illustrating that this method can be used to produce peptide functionalised nano-particulate titania